2013
DOI: 10.5194/angeo-31-1005-2013
|View full text |Cite
|
Sign up to set email alerts
|

A statistical study on O<sup>+</sup> flux in the dayside magnetosheath

Abstract: Abstract. Studies on terrestrial oxygen ion (O+) escape into the interplanetary space have considered a number of different escape paths. Recent observations however suggest a yet insufficiently investigated additional escape route for hot O+: along open magnetic field lines in the high altitude cusp and mantle. Here we present a statistical study on O+ flux in the high-latitude dayside magnetosheath. The O+ is generally seen relatively close to the magnetopause, consistent with observations of O+ flowing prim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
30
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 21 publications
(31 citation statements)
references
References 26 publications
(38 reference statements)
1
30
0
Order By: Relevance
“…The authors mentioned two transport processes leading to ion escape through the plasma sheet: a plasmoid that is formed by a tailward injection of a helical magnetic field structure and the transport of ions coming from the lobe or plasma mantle region to the distant neutral line. Other studies have shown that ion heating and acceleration in the cusp and mantle instead lead to escape into the magnetosheath for these ions (Nilsson et al, 2006Nilsson, 2011;Slapak et al, 2013). A statistical study on O + flux from Slapak et al (2013) estimated the total escape flux observed in the dayside magnetosheath to be ∼ 7 × 10 24 s −1 .…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations
“…The authors mentioned two transport processes leading to ion escape through the plasma sheet: a plasmoid that is formed by a tailward injection of a helical magnetic field structure and the transport of ions coming from the lobe or plasma mantle region to the distant neutral line. Other studies have shown that ion heating and acceleration in the cusp and mantle instead lead to escape into the magnetosheath for these ions (Nilsson et al, 2006Nilsson, 2011;Slapak et al, 2013). A statistical study on O + flux from Slapak et al (2013) estimated the total escape flux observed in the dayside magnetosheath to be ∼ 7 × 10 24 s −1 .…”
Section: Introductionmentioning
confidence: 98%
“…Other studies have shown that ion heating and acceleration in the cusp and mantle instead lead to escape into the magnetosheath for these ions (Nilsson et al, 2006Nilsson, 2011;Slapak et al, 2013). A statistical study on O + flux from Slapak et al (2013) estimated the total escape flux observed in the dayside magnetosheath to be ∼ 7 × 10 24 s −1 . Nilsson (2011) similarly estimated the escaping flux in the cusp and plasma mantle to be of the order of 10 25 s −1 .…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Zong et al (2001), Marcucci et al (2004), Kasahara et al (2008) and Slapak et al (2012). A statistical study of O + in the high-latitude dayside magnetosheath was made by Slapak et al (2013), showing that O + is common, contributing 0.7 × 10 25 s −1 to the total O + escape flux. The total O + escape flux of the mantles and the dayside magnetosheath is similar to the total O + cusp outflow flux of 2 × 10 25 s −1 , as reported by Yau and André (1997).…”
Section: Introductionmentioning
confidence: 99%
“…strongly northward IMF) in order for the mechanism to take place. Slapak et al (2013) made a statistical estimate of the total O + escape flux in the dayside magnetosheath, with the assumption that all observed O + would escape. A central question is whether this assumption is feasible or if O + trapping related to dual-lobe reconnection events is significant.…”
Section: Introductionmentioning
confidence: 99%